Análise tridimensional das dimensões da nasofaringe e orofaringe por diferentes métodos de mensuração e softwares - Torres, Hianne Miranda de (2017)
Introduction: The need to assess the pharyngeal airway space (PAS) during diagnosis and planning for orthodontic treatment and orthognathic surgeries led to the development of several measurement methods. However, the variability of methods and softwares limits comparisons of results derived from different studies. Thus, this study aimed to test measurement methods for the assessment of the nasopharynx and oropharynx using two different softwares. Methods: Forty cone beam computed tomographies (CBCTs) were selected from an image database of patients aged between 20-50 years, with the purpose of diagnosis or planning for orthodontic treatment with skeletal relationship Class I. A resin prototype of the nasopharynx and oropharynx was fabricated and served as gold standard to evaluate the accuracy of the results indicated by the software used. Two examiners performed measured the CBCTs independently. The sub regions of the nasopharynx and oropharynx were measured volumetrically according to the limits of five different measurement methods (3 methods for nasopharynx and 2 methods for oropharynx) and using two softwares (InVivoDental and Dolphin3D). The minimum area and the location of the minimum area were measured. The intra-rater and inter-rater agreement for measurements in the different methods and softwares were calculated using the intra-class correlation coefficient (ICC). ANOVA for repeated measures was used to compare the measurements of the 3 methods for the nasopharynx. The comparison of the 2 methods for the oropharynx and of the 2 softwares were performed using paired t-test. Statistical tests were performed at the 5% significance level using the software SPSS 22.0. Results: The intra-rater ICC ranged from 0.58 to 0.99. The inter-rater ICC ranged from 0.95 to 1.00. There was a statistically significant difference for the nasopharynx volume in the 3 methods of both softwares (P = 0.001). Both methods for oropharynx assessment were different considering the volume in both softwares (P = 0.001), the minimum area and location of the minimum area for software InVivoDental (P = 0.001). The two softwares showed statistically significant difference in the volume considering the nasopharynx and oropharynx methods (P < 0.05), except for the method 1 of the nasopharynx. There was also a difference for the minimum area in the method 5 of the oropharynx (P = 0.001), as well as to the location of the minimum area for all the nasopharynx and oropharynx methods (P < 0.05), except the method 4 of the oropharynx. When considering the prototype measurements as a reference, Dolphin3D software showed higher values theand InVivoDental software showed lower. Conclusion: The two softwares were reliable for the measurement of the variables assessed in this study. Different measurement methods could not be compared for the evaluation of the nasopharynx and oropharynx volumes. The results of volume and the location of the minimum area could not be compared between InVivoDental and Dolphin3D softwares. Dolphin3D software overestimate the volumetric values of the nasopharynx and oropharynx, while the InVivoDental software underestimate measurements.